2017
DOI: 10.1039/c7ra05584f
|View full text |Cite
|
Sign up to set email alerts
|

Controlled shaping of lipid vesicles in a microfluidic diffusion chamber

Abstract: The chemical environment around flaccid lipid vesicles, i.e., the osmotic conditions and the concentration of membrane-shaping molecules, is regulated only by diffusion without any hydrodynamic flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
3
7
1
Order By: Relevance
“…minnesota LPS has 7 acyl chains and a cylindrical shape. It has been shown that insertion of LPS alters the shape of lipid vesicles, causing concentration dependent shape fluctuations such as bead-like protrusions 53 . We speculate that conically-shaped lipid A moieties cause more alterations in the membrane structure than cylindrical ones.…”
Section: Discussionmentioning
confidence: 99%
“…minnesota LPS has 7 acyl chains and a cylindrical shape. It has been shown that insertion of LPS alters the shape of lipid vesicles, causing concentration dependent shape fluctuations such as bead-like protrusions 53 . We speculate that conically-shaped lipid A moieties cause more alterations in the membrane structure than cylindrical ones.…”
Section: Discussionmentioning
confidence: 99%
“…The spontaneous curvature model was originally introduced to describe the coupling between curvature and asymmetry of the membrane due to constituents' shapes or unequal distribution of constituents across the bilayer 6,52,53,58 . It was next implemented to describe the membrane curvature-dependent sorting of BAR protein amphiphysin 43 and membrane reshaping by lipopolysaccharide 59 . In the simplest form of this model, it is assumed that the protein-induced spontaneous curvature is coupled to the local protein concentration.…”
Section: Spontaneous Curvature Modelmentioning
confidence: 99%
“…Meticulous membrane transformation studies triggered by complex lipids are restricted to ganglioside (GM1), rhamnolipid-induced deformation, and glycocalyx [10,[17][18][19][20]. Previously, lipopolysaccharide (LPS)-induced transformations were reported in vesicles composed of lipids distantly mimicking physiological compositions and buffer conditions [21,22]. Notably, the morphologies in these reports [22] were observed even in the absence of LPS merely due to osmotic deflation.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, lipopolysaccharide (LPS)-induced transformations were reported in vesicles composed of lipids distantly mimicking physiological compositions and buffer conditions [21,22]. Notably, the morphologies in these reports [22] were observed even in the absence of LPS merely due to osmotic deflation. Moreover, spontaneous absorption of LPS into and out of lipid membrane of vesicles with no control over the process suggests an ambiguous role of LPS in the morphologies observed previously [21,22].…”
Section: Introductionmentioning
confidence: 99%